Gender roles in weblog online interaction among UiTM students / Jean Hoo Fang Jing, Nur'ain Mohsin and Rafidah Abdul Azis - Fang Jing, Jean Hoo; Mohsin, Nur'ain; Abdul Azis, Rafidah (Research Management Institute (RMI), 2011)
This study examined the gender roles on patterns of online interaction and organisation in weblogs for UiTM students. Twelve students, six male and six female from Faculty of Computer Science participated in the study. The aim of this study is to compare the gender differences based on the metalinguistic features used by the students to portray their identity online in the context of social construction. A qualitative research design was adopted in the data collection. This study implemented a single case study and Direct-observation was used as the instrumentation. Percentile was applied to measure differences and similarities of gender roles in the Weblog. The results indicated that there were no distinctive gender differences in the created weblog in this study. It can be concluded that the significance of this study is to view the ways weblog community is expected to interact (norms) based on gender roles in weblogs. Due to the fact that weblogs are easy to use, free to the public, and encourage self- expression as well as self-presentation, their application in the educational environment is worth considering.